Improving Speaking Skill By Using Telling Daily Activity Method At Mts Sirajul Huda Repok Sintung - Alniyati (INOVASI, 2025)
This research focuses on using music as a grammar learning medium without involving other learning elements such as gamification or additional digital technology. This study uses a descriptive quantitative method with a quasi-experimental approach. This approach is used to determine the effect of using music on students' interest and learning outcomes in English grammar. The data collected through pre-test and post-test, as well as a questionnaire to measure learning interest. This study used a pretest-posttest control group design with two groups: Experimental Group: Students are taught grammar using music media. Control Group: Students are taught grammar using conventional methods (without music). The result showed that the increase in learning interest was calculated by comparing the average scores of the questionnaire before and after treatment. The results of the analysis showed that the experimental group experienced a greater increase than the control group.